2007
DOI: 10.1143/jpsj.76.024703
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fermi Liquid Behavior in the Magnetotransport of CeMIn5 (M: Co and Rh): Striking Similarity between Quasi Two-Dimensional Heavy Fermion and High-Tc Cuprates

Abstract: We present a systematic study of the dc-resistivity, Hall effect, and magnetoresistance in the normal state of quasi two-dimensional (2D) heavy fermion superconductors CeMIn 5 (M: Rh and Co) under pressure. Here the electronic system evolves with pressure from an antiferromagnetic (AF) metal, through a highly unconventional non-Fermi liquid, and finally into a Fermi-liquid state. The novelty of these materials is best highlighted when compared with LaMIn 5 , a system with similar electronic structures, which s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 77 publications
(162 reference statements)
15
99
0
Order By: Relevance
“…The resonance peak observed by inelastic neutron measurement below T c supports the sign-reversing superconducting gap mediated by AF fluctuations [27,28]. Anomalous transport phenomena (such as Hall coefficient and Nernst signal) in the normal state in FeAs, which are similar to those observed in high-T c cuprates and CeM In 5 (M =Co, Rh, Ir) [29], also indicate the existence of strong AF fluctuations [10,12,30,31]. On the other hand, impurity effect on T c due to Co, Ni, or Zn substitution for Fe sites is very small or absent [11,12,[32][33][34], which is decisive for determining the pairing symmetry.…”
supporting
confidence: 72%
“…The resonance peak observed by inelastic neutron measurement below T c supports the sign-reversing superconducting gap mediated by AF fluctuations [27,28]. Anomalous transport phenomena (such as Hall coefficient and Nernst signal) in the normal state in FeAs, which are similar to those observed in high-T c cuprates and CeM In 5 (M =Co, Rh, Ir) [29], also indicate the existence of strong AF fluctuations [10,12,30,31]. On the other hand, impurity effect on T c due to Co, Ni, or Zn substitution for Fe sites is very small or absent [11,12,[32][33][34], which is decisive for determining the pairing symmetry.…”
supporting
confidence: 72%
“…47 Deviations from this standard behavior are also observed, for example, in CeRhIn 5 , where magnetoresistance violates Kohler's rule in the p region exhibiting prominent non-Fermi liquid properties, but satisfies a modified scaling relation. 48 From our partial analysis (not shown) on CeCu 2 Si 2 , no significant deviation from Kohler's rule throughout the investigated p range can be deduced. However, this preliminary statement still requires substantiation from supplementary data, especially at high p where ρ(T < 4 K) hardly varies, meaning that data points above 4 K should be included in order to perform the test on a broad parameter range.…”
Section: B Magnetoresistancementioning
confidence: 70%
“…Interestingly, an enhancement of ρ xy at low T is also reported in CeRhIn 5 close to the critical pressure p c ∼ p V and discussed in the light of the backflow effect in strongly correlated materials. 48 Further calculations within the critical VF scenario are currently carried out and may connect on a microscopic basis the observed increase of ρ xy (p) in vicinity of p V with the 4f electron delocalization and the proximity to the CEP in CeCu 2 Si 2 . agree with previous reports, 6,46,53 except that at p = 0 we obtain a slightly smaller signal from the A phase (not shown) compared to Ref.…”
Section: Transverse Resistivity: Hall Effectmentioning
confidence: 99%
“…It has been observed that the magnetoresistance in CeRhIn5 with similar electronic structure but weak electronic correlation obey the Kohler's rule 22 . It has also been observed that magnetoresistance strongly violates the Kohler's rule in the case of CeCoIn5 and CeRhIn5 33 .…”
Section: Mathematical Formulae Used In the Evaluationmentioning
confidence: 99%